Genetic diversity assessment of sorghum (Sorghum bicolor (L.) Moench) landraces using SNP markers. Issue 3 (26th May 2020) - Mengistu, Girma; Shimelis, Hussein; Laing, Mark; Lule, Dagnachew; Assefa, Ermias; Mathew, Isack
Abstract : Systematic genetic profiling of the genetic pool is fundamental to select desirable parents for conventional and genomic-assisted breeding. The objective of this study was to assess genetic variation and population structure in a diverse population of sorghum ( Sorghum bicolor (L.) Moench) accessions collected from various regions of Ethiopia. Using single nucleotide polymorphism (SNP) markers, potential breeding parents were then selected. In all, 342 sorghum accessions were genotyped using diversity array technology sequence-derived 5060 SNPs with > 5% minor allele frequency. Population structure, clustering, PCA, and analysis of molecular variance (AMOVA) were conducted to deduce variability within the germplasm. The AMOVA results revealed a higher percentage (58.8%) of variation among the populations followed by variation within accessions (40.4%). Polymorphic information content (PIC) values ranged from 0.184 for accessions collected from the Somali to 0.260 for the Oromia and Southern Nations, Nationalities, and Peoples (SNNP) regions. Higher genetic variation was detected among sorghum collections from Oromia followed by those of the SNNP region. The selected SNP markers were the most powerful in discriminating the tested sorghum accessions. Population structure analysis revealed the presence of two main distinct genetic clusters in which accessions were grouped based on area of collection. The present findings indicated abundant genetic variability among Ethiopian sorghum accessions, confirming that they will be useful for breeding, germplasm conservation and genomic selection.